Family interview for organ and tissue donation: good practice assumptions - Neide da Silva Knhis; Sabrina Regina Martins; Aline Lima Pestana Magalhães; Saulo Fábio Ramos; Camila Telemberg Sell; Clarice Koerich; Laura Calvacanti de Farias Brehmer
ABSTRACT Objectives: to identify information that can support creating good practice assumptions to develop family interview for organ and tissue donation. Methods: this scoping study, conducted in two Brazilian hospitals in the southern, between April and December 2017, included integrative review and consultation with 15 families who experienced interview for organ donation. For data analysis, thematic content analysis was used. Results: three categories emerged: communication of death, which shows the need to know the history of hospitalization of patients; emotional support, the team must have mastery of the stages of mourning; information about donation, professionals need to know the stages of the donation process and respect families' time. Final Considerations: good practice assumptions point to the need for team training, respect for family time and the use of simple language.